Relationship between Sociodemographic Factors and MotherÃ¢â¬â¢s Participation in Breast Feeding Support Group with Exclusive Breastfeeding Success in Banyuwangi - Wardani, Endah Kusuma; Hastuti, Uki Retno Budi; Adriani, Rita Benya (Journal of Maternal and Child Health, 2017)
Background: Exclusive breastfeeding for 6 months is every babyÃ¢â¬â¢s right as it can save the babys life and have a good impact on mothers health. The coverage of exclusive breastfeeding in Banyuwangi in 2015 was 78.7%. This study aims to explain the relationship between age, parity, education, occupation, household assistant (ART), mother participation in maternal breast support group (KP-ASI) and exclusive breastfeeding success.Subjects and Methods: This was an analytic observational study with cross sectional design. The study was conducted in 3 Puskesmas (community health center) in Banyuwangi. The study time was August to September 2017. The sample size was 120 subjects, selected by simple random sampling technique with the total of case group 40 and control group 80. The dependent variable was the exclusive breastfeeding (ASI) success. Independent variables were age, parity, education, occupation, ART, mother participation in KP-ASI. The data was analyzed using multiple logistic regressions.Result: MotherÃ¢â¬â¢s age (OR = 3.99; 95% CI = 1.08 to 14.64; p = 0.037), parity (OR = 7.15; 95% CI = 2.19 to 23.33; p = 0.001), education (OR = 1.30; CI95% = (OR = 0.99; 95% CI = 0.16 to 2.35; p = 0.488), household assistant (OR = 8.99; 95% CI = 2.32 to 34.88; p = 0.001); motherÃ¢â¬â¢s participation in breastfeeding (OR = 5.32; 95% CI = 1.79 to 15.76; p = 0.003) was related to exclusive breastfeeding success.Conclusions: The exclusive breastfeeding success is related to motherÃ¢â¬â¢s age, parity, household assistant, and motherÃ¢â¬â¢s participation in breastfeeding, but not significantly related to motherÃ¢â¬â¢s education and employment.Keywords: Exclusive breast feeding, Sociodemographic factors, KP-ASICorrespondence:ÃÂ EndahKusumaWardani. Masters Program in Public Health, SebelasMaret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: qsuma89@yahoo.com. Mobile: +6282257193736.Journal of Maternal and Child Health (2017), 2(4): 335-344https://doi.org/10.26911/thejmch.2017.02.04.05ÃÂ